John P. Kotter on what leaders really do - Kotter, John P., 1947- (Boston : Harvard Business School Press, 1999)
"With the relentless change and escalating uncertainty that define our times, the need for strong leadership in business, government, and society has never been greater. Careers, customers, and communities all suffer in a poorly run enterprise. Sure to be eagerly embraced by Kotter's huge global following, John P. Kotter on What Leaders Really Do provides an invaluable opportunity to consider the core issues that lie at the heart of leadership and to rethink our own relationship to the work of leaders."--BOOK JACKET.
Leadership at the turn of the century -- Leadership and change -- Choosing strategies for change -- What leaders really do -- Leading change: why transformation efforts fail -- Dependency and networks -- Power, dependence, and effective management -- Managing your boss -- What effective general managers really do.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Leadership; Management; Leiderschap; Leadership; Leadership; Entreprises -- Direction générale; Leadership; Management; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books